Ketentuan Penyerahan Wasiat Wajibah Kepada Ahli Waris Yang Berbeda Agama di Pengadilan dan Pertimbangan Hakim Dalam Putusan Pengadilan Agama Bekasi - Nabila Khalisha; Rahmi Zubaedah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
The article discusse about the distribution of inheritance between religions through the provision of wasiat wajibah to non-Muslim husband in the Bekasi Religious Court Decision Number 0024 / Pdt.P / 2016 / PA.Bks due to the legal discovery (rechtsvinding) originating from the ijtihad method of the Court's decision Agung Number 368 / K / AG / 1995. This legal discovery (rechtsvinding) exists because the distribution of inheritance between religions is not regulated in the Civil Code, even in the Islamic Law Compilation itself, inheritance and inheritance of inheritance between heirs and heirs of different religions is not allowed. the reason is because religious differences become one of the hijabs or a barrier for someone to become an heir. This study aims to determine the provisions of the provision of a compulsory will to a person without an heir before he / she dies, and the considerations used by the judge in the Bekasi Religious Court Decision Number 0024 / Pdt.P / 2016 / PA.Bks. The research method used juridical normative, because written rules and regulations through observations carried out are closely related to the literature because requires secondary data. The research get the result from this method.